Urinary Eicosanoid Metabolites in HIV-Infected Women with Central Obesity Switching to Raltegravir: An Analysis from the Women, Integrase, and Fat Accumulation Trial. (1st June 2014) - Hulgan, Todd; Boger, M. Sean; Liao, Diana H.; McComsey, Grace A.; Wanke, Christine A.; Mangili, Alexandra; Walmsley, Sharon L.; McCreath, Heather; Milne, Ginger L.; Sanchez, Stephanie C.; Currier, Judith S.; Lake, Jordan E.
Abstract : Chronic inflammation is a hallmark of HIV infection. Eicosanoids reflect inflammation, oxidant stress, and vascular health and vary by sex and metabolic parameters. Raltegravir (RAL) is an HIV-1 integrase inhibitor that may have limited metabolic effects. We assessed urinary F2 -isoprostanes (F2 -IsoPs), prostaglandin E2 (PGE-M), prostacyclin (PGI-M), and thromboxane B2 (TxB2 ) in HIV-infected women switching to RAL-containing antiretroviral therapy (ART). Thirty-seven women (RAL = 17; PI/NNRTI = 20) with a median age of 43 years and BMI 32 kg/m 2 completed week 24. TxB2 increased in the RAL versus PI/NNRTI arm (+0.09 versus −0.02; P = 0.06 ). Baseline PGI-M was lower in the RAL arm (P = 0.005 ); no other between-arm cross-sectional differences were observed. In the PI/NNRTI arm, 24-week visceral adipose tissue change correlated with PGI-M (rho = 0.45 ; P = 0.04 ) and TxB2 (rho = 0.44 ; P = 0.005 ) changes, with a trend seen for PGE-M (rho = 0.41 ; P = 0.07 ). In an adjusted model, age ≥ 50 years (N = 8 ) was associated with increased PGE-M (P = 0.04 ). In this randomized trial, a switch to RAL did not significantly affect urinary eicosanoids over 24 weeks. In women continuing PI/NNRTI, increased visceral adipose tissue correlated with increased PGI-M and PGE-M. Older age (≥50) was associated with increased PGE-M. Relationships between aging, adiposity, ART, and eicosanoids during HIV-infection require further study.